The Naturally Evolved EPSPS From Goosegrass Confers High Glyphosate Resistance to Rice - Ouyang, Chao; Liu, Wei; Chen, Silan; Zhao, Huimin; Chen, Xinyan; Jin, Xiongxia; Li, Xinpeng; Wu, Yongzhong; Zeng, Xiang; Huang, Peijin; He, Xiuying; An, Baoguang (Frontiers in Plant Science, 2021)
Glyphosate resistant (GR) crops developed by the CP4-EPSPS gene from Agrobacterium have been planted on a massive scale in the world, which benefit from the high efficiency and broad-spectrum of glyphosate on weed control. Some GR genes from microbes have been reported, which might raise the biosafety concerns. Most of them were obtained through hygromycin-HPT transformation system yet. Here we reported the plant source EPSPS gene from googegrass endowed rice with high resistance to glyphosate. The integrations of transgenes in the rice genome and the inheritability were investigated within two generations. The EiEPSPS transgenic plants displayed similar growth and development to wild type under no glyphosate selection pressure but better reproductive performance under lower glyphosate selection pressure. Furthermore, we reconstructed a binary vector pCEiEPSPS and established the whole stage glyphosate selection by the vector. The Glyphosate-pCEiEPSPS selection system showed significantly higher transformation efficiency compared with the hygromycin-HPT transformation system. Our results provided a promising alternative gene resource to the development of GR plants and also extended the plant transformation toolbox.